DESCRIPTION OF MOTHER'S KNOWLEDGE ABOUT THE OCCURRENCE ISPA IN TODDLERS IN BUNGA TANJUNG VILLAGE - Pratiwi, Aisyah; Nanjar, Icmi Ikhtiari; Setiawan, Nita Anggerina Putri Hi (Cattleya Darmaya Fortuna, 2025)
In Indonesia, based on a monitoring survey, pneumonia contributes to almost one-fifth of child deaths worldwide and 2 million toddlers die each year, the majority of which occur in African and Southeast Asian countries. Acute respiratory tract infection (ARI) is an inflammatory disease of the throat that lasts up to 14 days which can be transmitted through saliva, blood, sneezing or respiratory air containing germs inhaled by healthy people. This research is descriptive using primary data. The population in this research is all mothers who have toddlers in Bunga Tanjung village. Sampling was carried out using a total sampling technique, with a sample of 40 mothers who have toddlers in Bunga Tanjung village. The results of the study showed that the majority of mothers who have toddlers based on knowledge were 25 mothers (62.5%), the majority on education were 25 mothers (62.5%), the majority at the level of information sources were 20 mothers (50%), the majority based on age were 25 mothers (62.5%). the majority based on occupation were 28 mothers (70%). Mothers who have toddlers are expected to be more attentive to matters related to their toddlers' health, especially those who suffer from ISPA.